Quality of care for people with multimorbidity - a case series - Michaela L. Schiøtz; Dorte Høst; Mikkel B. Christensen; Helena Domínguez; Yasmin Hamid; Merete Almind; Kim L. Sørensen; Thomas Saxild; Rikke Høgsbro Holm; Anne Frølich (BMC, 2017)
Abstract Background Multimorbidity is becoming increasingly prevalent and presents challenges for healthcare providers and systems. Studies examining the relationship between multimorbidity and quality of care report mixed findings. The purpose of this study was to investigate quality of care for people with multimorbidity in the publicly funded healthcare system in Denmark. Methods To investigate the quality of care for people with multimorbidity different groups of clinicians from the hospital, general practice and the municipality reviewed records from 23 persons with multimorbidity and discussed them in three focus groups. Before each focus group, clinicians were asked to review patients' medical records and assess their care by responding to a questionnaire. Medical records from 2013 from hospitals, general practice, and health centers in the local municipality were collected and linked for the 23 patients. Further, two clinical pharmacologists reviewed the appropriateness of medications listed in patient records. Results The review of the patients' records conducted by three groups of clinicians revealed that around half of the patients received adequate care for the single condition which prompted the episode of care such as a hospitalization, a visit to an outpatient clinic or the general practitioner. Further, the care provided to approximately two-thirds of the patients did not take comorbidities into account and insufficiently addressed more diffuse symptoms or problems. The review of the medication lists revealed that the majority of the medication lists contained inappropriate medications and that there were incongruity in medication listed in the primary and secondary care sector. Several barriers for providing high quality care were identified. These included relative short consultation times in general practice and outpatient clinics, lack of care coordinators, and lack of shared IT-system proving an overview of the treatment. Conclusions Our findings reveal quality of care deficiencies for people with multimorbidity. Suggestions for care improvement for people with multimorbidity includes formally assigned responsibility for care coordination, a change in the financial incentive structure towards a system rewarding high quality care and care focusing on prevention of disease exacerbation, as well as implementing shared medical record systems.